42When to implant CRT-P or CRT-D in the elderly?. (18th June 2020) - Silverio Antonio, P; Nunes-Ferreira, A; Aguiar-Ricardo, I; Rodrigues, T; Rigueira, J; Santos, R; Cunha, N; Couto Pereira, S; S Morais, P; Magalhaes, A; Bernardes, A; J Pinto, F; et al.
Abstract: Introduction: Cardiac resynchronization therapy (CRT) in elder patients is increasingly common. However, the decision to implant a device with defibrillator in these patients is often complex and it can be limited not only by the shorter life expectancy but also by a lower relative risk of arrhythmic compare to non‐arrhythmic death due to other comorbidities. Thus, wether CRT is effective in an elderly population (≥75 years old), or if a defibrillator (CRT-D versus CRT-P) influences outcomes is a pivotal concern needing additional data. Purpose: To compare the prognostic impact of CRT-P vs CRT-D in old patients (≥ 75 years old) and its impact in the response rate to CRT. Methods: A prospective single-center study was conducted of patients indicated for a CRT implant since 2015. Demographic and clinical criteria were evaluated. Transthoracic echocardiography was performed before CRT implant and between 6-12 months post-implant. Patients with an ejection fraction (EF) elevation ≥ 10% or a LV end-systolic volume (ESV) reduction ≥ 15% were classified as responders. Patients with EF elevation ≥ 20% or LV ESV reduction ≥ 30% were classified as super-responders. Time to surgical revision and mortality were evaluated using the Cox regression and Kaplan-Meier methods. The decision to implant a CRT-P or CRT-D device was made according to clinical decision. Prognostic impact of CRT-P vs CRT-D was evaluated by comparing total mortality using the Cox regression and Kaplan-Meier methods. Results: From 2015-2019, 566 CRTs were implanted (26.1% female, follow-up duration 18.9 ± 15.8 months). Among these patients, 53.5% had < 75 years old and 46.5% ≥ 75 years. Baseline clinical characteristics were similar, except for a higher prevalence of chronic kidney disease and atrial fibrillation in the elderly population. The proportion of CRT-D/CRT-P was different between these groups (p < 0.001): in the elderly group, more CRT-P were implanted (67.6% vs 32.4 CRT-D) and in the younger group more CRT-D were implanted (77.9% vs 22.1% CRT-P). The prevalence of complications due to CRT implant was similar in the two groups (4.7% vs 4.2%, p = NS) but the need for surgical revision was less frequent in the elderly group (11.0% vs 5.7%, p = 0.03). The CRT response rate was equivalent in both groups (40.1% vs 59.9%, p = NS), as was the super-response rate (33% in young vs 26.5% in old patients, p = NS). In the elderly population, the 4-year survival rate was similar between CRT-P and CRT-D patients (75.4% vs 79.8%). Conclusion: Patients older than 75 years old have similar benefits from the CRT as patients < 75 years, with equivalent response rates to CRT. However, judging from the similar prognostic impact of CRT-P vs CRT-D in this elder population, the implant of a defibrillator should be personalized.